Supratherapeutic Dosing of Acetaminophen in Iranian Hospitalized Adult Patients: Supratherapeutic dosing of Acetaminophen - Moghaddam, Arash Afshari; Sheybani, Fereshte; Behboudifar, Atefeh; Naderi, HamidReza; Morovatdar, Negar; Dadpour, Bita; Khosravi, Nasrin; Rashid, Javad; Hoseini, Masoumeh (Iranian Journal of Pharmaceutical Sciences, 2019)
Acetaminophen is the most commonly used analgesic and fever-lowering agent that is prescribed in a high percentage of patients. Due to the high prevalence of the administration of this drug, even a small percentage of errors in prescription can be significant and have important implications. The aim of the present study was to determine the frequency of supratherapeutic dosing of acetaminophen among hospitalized adult patients and its association with clinical outcomes. We conducted a retrospective, cross sectional study of all hospitalized adult patients in a teaching hospital affiliated to Mashhad University of Medical Sciences, Mashhad, Iran. During the three-month study period, 4,781 (24.83%) out of 19,252 hospitalized cases received acetaminophen. Of those who received acetaminophen, 264 (5.5%) cases received a supratherapeutic dose at least once. Of 611 incidences of supratherapeutic dosing, 99.1% occurred in surgical wards and surgical intensive care units (ICUs), and 98.8% was associated with receiving parenteral formulations of acetaminophen. Multivariate analysis indicated supratherapeutic dosing of acetaminophen was significantly associated with multiple factors including female gender, older age, and longer length of hospital stays. All things considered, the percentage of hospitalized adult patients who received any dose of acetaminophen at our center was considerably less than other countries. Despite this, the frequency of instances of supratherapeutic dosing of this medication was significant (i.e. 17.6 days per 1,000 patient-days). Considering recent reports concerning the risk of hepatotoxicity associated with the repeated use of supratherapeutic doses of acetaminophen, continuous monitoring of acetaminophen utilization in order to prevent these instances is needed. Furthermore, based on the low percentage of patients who receive acetaminophen at our center, conducting research to study the pattern of prescription of analgesics and antipyretics in our center and its association with clinical outcome is logical.